Exploratory laparoscopy at suspicion of acute appendicitis. Review - Andren-Sandberg, A; Ryska, M (Rozhledy v chirurgii, 2004)
Exploratory laparoscopy has been used since 1910 and is one of the new tools for diagnosing appendicitis on a routine basis. It can be looked upon as "semi-invasive" in comparison to on one hand ultrasonography/CT/MRI and on the other open laparotomy. According to the literature, mostly in retrospective studies, laparoscopy might reduce the frequencies of unnecessary appendectomies in 20-30 percent and an accuracy of diagnosis of appendicitis of 95-99 percent. This means that laparoscopy has a sensitivity of 92 percent in diagnosing acute appendicitis, including all cases of mucosal inflammation only. This means, however, that about one in 11 appendicitis is missed and it is still a question as to whether an appendix that looks normal at laparoscopy for acute right iliac fossa pain should be removed, or whether if it is not removed, there is a risk of missing an early case of appendicitis later leading to perforation and peritonitis? Mucosal inflammation obviously can never be determined in the appendix is left in place. However, a summery of available data seems to favour that it is distinctly uncommon that explorative laparoscopy misses any acute appendicitis that requires appendectomy. If there are cases of acute appendicitis not requiring appendectomy can only be known in prospective studies. A Cochran review was published in early 2002 and analysed 45 randomized trials, 39 of which had been carried out in adults, comparing both therapeutic and diagnostic outcomes of patients undergoing open or laparoscopic surgery for suspected appendicitis. Diagnostic outcomes favoured the laparoscopic approach in that both the negative appendectomy rate and "the frequency of an unestablished diagnosis" were reduced, most significantly in women in their reproductive years. However, in the conclusion the authors sounded a note of caution about the quality of some of the research data they had analysed, and recommended that more blinded studies be performed. Because there is a belief that laparoscopic appendectomy is less likely to cause intraperitoneal adhesions than open surgery, they also recommended longer follow-up studies to assess the relative incidences of obstruction due to adhesions resulting from the two techniques. Therefore, the conclusion can be drawn that in all equivocal cases laparoscopy is better than laparotomy as the initial step in year 2003. However, there is still a lack of data comparing non-invasive modern techniques such as ultrasonography and CT with laparoscopy, and the value of laparoscopy after the best available ultrasonography or CT.
Keywords: akutní nemoc; laparoskopie; Appendicitis; lidé; Acute Disease; Laparoscopy; apendicitida; Humans